POLA TABUHAN TUMA’ DALAM RITUAL BASUAYAK SUKU DAYAK KANAYATN DI DESA CAPKALA KECAMATAN CAPKALA KABUPATEN BENGKAYANG - Arbilianto, Arbilianto; Ghozali, Imam; Silaban, Chiristianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this research is the decrease of youth generation’s interest to the traditional art as ancestors’ heritage so that appear the effort to conserve the traditional musical where one of them is almost extincted and unknown by their society. The purpose of this research is to describe the pattern of Tuma’ percussion in Basuayak tradition to Dayak Kanayatn tribe in Capkala village, Capkala district, Bengkayang regency. The method of this research is Descriptive method in qualitative form through Ethnomusicology Approach. The research data is (1) the performance of percussion pattern in Basuayak tradition. (2) The instrument of Dau We’, Dau Anak dan Tuma’. (3) The musical structure of Basuayak theme, motive, musical measure, tone, tempo, dynamics and phrase. The result of this research is (1) there are two musical instruments used into Pulo Pinang art, they are eight Dau and Gong with three pattern of Tuma’ percussion, Bawakng pattern, Jubata pattern, batu berapi pattern. (2) The notation of Bawakng percussion, Jubata percussion, and batu berapi percussion uses musical score in Bar notation form. Keywords: Pulo Pinang, Music Structure